Implementation of Lean Construction to Reduce Waste with the Value Stream Analysis Tools (VALSAT) Method in the Project Casting Process - Lestari, Yetty Dwi; Adhirajasa, Ananda Rizqullah (Southeast Asian Business Review, 2024)
This study aims to identify waste that occurs in the casting process of the project carried out by CV. Wishitama using value stream analysis tools (VALSAT) and provide suggestions for improvements with fishbone diagrams for the casting process of the project carried out by CV. Wishitama. This study uses a qualitative approach and case study with value stream analysis tools (VALSAT) and fishbone diagram analysis. The results of this study are that there are four types of waste that are prioritized for elimination, namely, overprocessing, defective products, queues, and motion. This study will provide new contributions to knowledge in the field of lean construction, with a focus on the construction industry. The results of this study will complement existing knowledge and provide new insights into how the application of lean construction can eliminate waste in the construction industry. Companies can eliminate and be effective in waiting for heavy equipment (readymix and concrete pumps) and vibrating equipment during casting. In addition, companies can increase direct supervision, conduct additional training, conduct evaluations, implement a reward or punishment system according to employee performance, plan efficient schedules, assign employees according to needs, and conduct outreach on current employee performance as a form of effort to improve human resources.